Cholecystectomy is associated with a higher risk of irritable bowel syndrome in the UK Biobank: a prospective cohort study - Zhao, Jinyu; Tian, Liang; Xia, Bin; Mi, Ningning; He, Qiangsheng; Yang, Man; Wang, Danni; Wu, Siqing; Li, Zijun; Zhang, Shiyong; Zhang, Xianzhuo; Yue, Ping; et al. (Frontiers in Pharmacology, 2023)
Background: Recent studies have shown that bile acids are essential in irritable bowel syndrome (IBS) pathology, and cholecystectomy has direct effects on bile acid metabolism. However, whether cholecystectomy increases the risk of IBS remains unclear. We aimed to investigate the association between cholecystectomy and IBS risk in the UK Biobank (UKB). Methods: This study is a prospective analysis of 413,472 participants who were free of IBS, inflammatory bowel disease, cancer, or common benign digestive tract diseases. We identified incidents of IBS through self-reporting or links to primary health care and hospitalization data. We evaluated hazard ratios (HRs) adjusted for sociodemographic characteristics, health behaviours, comorbidities, and medications. Results: During a median follow-up period of 12.7 years, we observed 15,503 new cases of IBS. Participants with a history of cholecystectomy had a 46% higher risk of IBS than those without (HR = 1.46, 95% CI: 1.32-1.60), and further subtype analysis showed that the risk of IBS with diarrhoea was significantly higher than the risk of IBS without diarrhoea (HR = 1.71, 95% CI: 1.30-2.25 vs. HR = 1.42, 95% CI: 1.28-1.58). The overall covariate-adjusted HRs for IBS were similar between the group with both cholecystectomy and gallstones (HR = 1.45, 95% CI: 1.32-1.58) and the group with cholecystectomy without gallstones (HR = 1.50, 95% CI: 1.36-1.67) when the group without both cholecystectomy and gallstones was used as a reference. The overall covariate-adjusted HR was not significantly different in the group without cholecystectomy with gallstones (HR = 1.18, 95% CI: 0.95-1.47). The positive association of cholecystectomy with IBS risk did not change when stratifying the data based on age, sex, BMI, smoking, alcohol consumption, healthy diet, quality sleep, physical activity, type 2 diabetes, hypertension, hyperlipidaemia, mental illness, NSAID intake, or acid inhibitor intake. Sensitivity analyses, including propensity score matching analysis and lagging the exposure for two/four years, indicated that the effects were robust. Conclusion: Cholecystectomy was associated with a higher risk of IBS, especially IBS with diarrhoea. Additional prospective randomized controlled and experimental studies are warranted to further validate the association and to explore the relevant biological mechanisms.